The Englishization of Higher Education in Europe - Wilkinson, Robert; Gabriëls, René (Amsterdam University Press, 2021)
The introduction of English as a medium of instruction (EMI) has changed higher education enormously in many European countries. This development is increasingly encapsulated under the term Englishization, that is, the increasing dispersion of English as a means of communication in non-Anglophone contexts. Englishization is not undisputed: legal challenges have arisen in several countries. Nor is it uniform; universities across Europe embrace Englishization, but they do so in their own way. In this volume, authors from 15 European countries present analyses from a range of perspectives coalescing around core concerns: the quality of education, cultural identity, inequality of opportunities and access, questions of justice and democracy, and internationalization and language policy. This book will appeal to researchers in applied linguistics, sociolinguistics, educational sciences, and political science, as well as policy makers and people with a concern about the direction of higher education.